NEW YORK STATE TAX INCREASE (Tufts Archival Research Center, 2007)
Lorillard report summarizing the impact of New York's increase in cigarette excise taxes on the tobacco industry, cigarette manufacturers, and specific brands. Provides background on tax. Finds that discount brands have become more popular, that the sales volume has decreased since the same time last year, and that sales have increased on Native American Reservations. Charts detailed findings. Recommends next steps.